Effects of Age and Dietary Factors on the Blood Beta-Hydroxybutyric Acid, Metabolites, Immunoglobulins, and Hormones of Goats - Abdelsattar, Mahmoud M.; Vargas-Bello-Pérez, Einar; Zhuang, Yimin; Fu, Yuze; Zhang, Naifeng (Frontiers in Veterinary Science, 2022)
The study was aimed to examine the effects of age and dietary beta-hydroxybutyric acid (BHBA) on blood BHBA and blood health indicators in goat kids. Thirty male goats of five ages (1, 2, 3, 6, and 12 months old) were selected for blood sampling to determine the influence of age. Another 64 goat kids (half males and half females) were weaned at 1 month old and fed with starter diets with control, low, medium, and high BHBA doses (0, 3, 6, and 9 g/animal/day, respectively). Six goats per treatment were selected for blood analysis at 2 and 3 months of age. There were significant effects (p < 0.01) of ages on the blood parameters of goat kids. The 6- and 12-month-old goats showed significantly lower blood total protein, globulin, BHBA, IgA, and IgM concentrations than did young goats, while they had a higher albumin-to-globulin ratio than young goats. The blood glucose decreased (p < 0.01) and IgG increased over time (p < 0.01). In blood, growth hormone (GH) and insulin-like growth factor I (IGF-I) were lower (p < 0.01) at 1- and 3-month-old goats than 12-month-old goats. The high dietary BHBA improved (p < 0.05) the ratio of albumin to globulin of 2-month-old kids compared with control. The blood GH and IGF-I were lower (p < 0.01) in the medium BHBA dose at 2 months of age than control. These results suggested that age greatly impacted blood composition, especially around weaning, and dietary BHBA showed beneficial regulating effects on blood total protein level in young goats.